Don't judge a fish by its fins: species delineation of Congolese Labeo (Cyprinidae). (31st December 2016) - Van Steenberge, Maarten; Gajdzik, Laura; Chilala, Alex; Snoeks, Jos; Vreven, Emmanuel
Abstract : Conspicuous characters are often useful in species identification. Yet, identification and delineation are two different processes, and such characters do not necessarily provide the best basis on which species can be delineated. This is illustrated by the case of the Labeo with papillary lips from the Congo basin. Traditionally, species delineation in this group was based on a conspicuous trait: the shape of the dorsal fin, which shows a profound degree of differentiation. Morphometric analyses were performed on 185 specimens both with and without measurements taken on this fin. The groups obtained using these two approaches were compared with those obtained through DNA barcoding. For this, 24 sequences of the standard barcoding COI gene were obtained. Species delineations based on morphological and molecular results were in agreement when the shape of the dorsal fin was ignored. This suggested that of the five nominal species known from the Congo basin, L. altivelis, L. rosae, L. lineatus, L. weeksii and L. maleboensis, only the former three remain valid. Consequently, L. weeksii was synonymised with L. altivelis and L. maleboensis with L. lineatus . The sole Congo basin endemic is L. lineatus as L. altivelis and L. rosae also occur in more southern basins. The use of the shape of the dorsal fin in morphological studies has previously led to overestimates of species diversity in this group. This is due to the fact that L. altivelis shows a remarkable amount of geographical variation for this trait. The large amount of intra‐ and interspecific variation in this character was caused by differential allometric growth in different parts of the dorsal fin.